Child Rights and Human Security: Promoting Child Protection At The Tourist Attractions On Madura - Rusmilawati Windari; Tolib Effendi (Research Collaboration Community (RCC), 2021)
Tourism nowadays is a promising as well as challenging industry. The need for having leisure, relaxation, and inner satisfaction is not of the tertiary nature, but the primary one. Each country, of course, is actively improving its own tourist attractions for its economic growth. Madura, as a big island in East Java with many tourist attractions, is in a continuous improvement in the last five years. Unfortunately, child protection has not been considered a significant part of the designing of good tourism. Given that children are the main targets of tourism, good, peaceful tourism will be realized with the fulfillment of child rights at the tourist attractions. This paper is a socio-legal research work that uses primary data from observations and interviews with relevant respondents. All of the data are analyzed in a descriptive-qualitative manner. This paper aims at exploring and analyzing the efforts made by local governments in promoting child protection through human security at the tourist attractions on Madura. Moreover, it also describes the obstacles faced by these local governments along with some solutions to such obstacles. The main finding is Sampang Regency has initiated a role of the service in charge in child protection, which is currently assumed by the Social Service, across all regional strategic development fields, including the tourism sector.